PENGARUH PROFITABILITAS DAN SIZE TERHADAP NILAI PERUSAHAAN DENGAN CSR SEBAGAI VARIABEL PEMODERASI - Pramana, I Gusti Ngurah Agung Dwi; Mustanda, I Ketut (E-Jurnal Manajemen, 2016)
The purpose of this study was to determine the significance of the effect on the Company's profitability and the size of the company's value, determine the role of CSR in moderating influence on the company's profitability and the size of the participating companies the value of Indonesian Sustainability Reporting Award (ISRA). This study sampled 21 companies during the study period is 2011-2013 by using purposive sampling method. The analysis technique used is the Absolute Difference Test Value. The test results show that the hypothesis of profitability, company size, and CSR partially affect the value of the company, in which the size of the company's profitability and positive influence whereas CSR negative effect. Additionally result that profitability is significantly positive effect on the value of the Company, Company Size significantly positive effect on Company Values, and Corporate Social Responsibility (CSR) is significantly negative effect on the value of the Company and CSR is able to moderate the effect of profitability on the value of the company, but not able to moderate the effect of company size on the value of the company
Keywords: Profitability, Company Size, CSR, Corporate Value